Subclinical left ventricular deterioration in patients with erectile dysfunction. Issue 5 (1st October 2016) - Karagöz, Ahmet; Günaydin, Zeki Yüksel; Bektaş, Osman; Benli, Erdal; Kaya, Ahmet
Abstract : Objective The majority of risk factors for CAD are also encountered in patients with erectile dysfunction (ED). We aimed to investigate a possible association between left ventricular contraction dynamics and ED using speckle tracking echocardiography. Methods and results A total of 125 patients with ED were compared with 40 age- and sex-matched control subjects. ED was evaluated using the International Index of Erectile Function questionnaire. STE and global longitudinal strain (GLS) were assessed from two-, three- and fourchamber apical images while global circumferencial strain (GCS) was evaluated using the parasternal short-axis images in left ventricular basal, mid and apical levels. GLS and GCS were detected to be more impaired in the ED group compared to controls (–17.3 ± 2.6 vs –20.8 ± 3.5, P < 0.05; –19.3 ± 4.5 vs –21.3 ± 3.7, P < 0.05, respectively). Systolic longitudinal and circumferential strain rates were also higher in the ED group compared to the controls (–1.2 ± 0.3 vs –1.7 ± 0.2, P < 0.005; –1.3 ± 0.3 vs –1.6 ± 0.5, P < 0.05, respectively) while longitudinal early and late diastolic strain rates were lower (1.3 ± 0.8 vs 2.4 ± 0.8, P < 0.05; 0.9 ± 0.3 vs 1.4 ± 0.2, P < 0.05 respectively). Circumferential early and late diastolic strain rates were similar between the two groups. Conclusions ED is associated with an increase in GLS and GCS even in the absence of overt CAD. Moreover, LV systolic dysfunction increases with increasing severity of ED. Strain and strain rate imaging seem to be a valuable method in the definition of high-risk patients.